Winning applicants and influencing job seekers: an introduction to the special issue on employer branding and talent acquisition - Yu, Kang Yang Trevor (2023)
This article introduces the special issue in Human Resource Management featuring employer branding and talent acquisition. We provide a brief history of talent acquisition and introduce an employer branding approach to this process, especially emphasizing the potential of this approach for building competitive advantage. The challenges of employer branding on social media in the digital age are also highlighted. We then introduce the five papers contained in this issue, each representing a variety of levels of analysis, theoretical perspectives, environmental contexts, and methodological and design approaches to scholarly investigations on this topic. Our introduction concludes with a list of research questions characterizing an agenda for future research based aroundthe themes of (i) macro contextual effects; (ii) strategic employer branding; (iii) psychology and processing of employer brands; (iv) role the time; and (v) methods and approaches.